2014
DOI: 10.1007/s10021-014-9798-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Constraints on the Decomposition of Fagus sylvatica Leaf Litter Along an Altitudinal Gradient in Contrasting Land-Use Types

Abstract: Climate change can affect the process of carbon cycling and leaf litter decomposition in multiple ways, both directly and indirectly, though the strength and direction of this relationship is often context dependent. In this experiment, we followed decomposition of a standard litter type-senescent leaves of Fagus sylvatica collected from a single location-along a 1000 m altitudinal gradient of four sites over 2.5 years. To control the edaphic conditions, we transplanted intact turf mesocosms from three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…In winter, in the subalpine grassland studied, water is not limiting for C-activities and so under these conditions resource availability appeared to limit SOM enzymatic activity (Brooks et al, 2005;Harrysson Drotz et al, 2009;Öquist and Laudon, 2008). Such relationships between microbial activity and abundance and WEOC/DOC content have been reported earlier (Marschner and Kalbitz, 2003;Rees and Parker, 2005), but surprisingly the WEOC degree of aromaticity normally used as a proxy of WEOC biodegradability (Marschner and Kalbitz 2003) was not found as a driver of soil enzyme activity under the climate change (Gavazov et al, 2014). The accumulation of freePOM due to lower enzyme potential activities (Fig 4.B) adds further support for fresh plant material accumulation.…”
Section: -Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In winter, in the subalpine grassland studied, water is not limiting for C-activities and so under these conditions resource availability appeared to limit SOM enzymatic activity (Brooks et al, 2005;Harrysson Drotz et al, 2009;Öquist and Laudon, 2008). Such relationships between microbial activity and abundance and WEOC/DOC content have been reported earlier (Marschner and Kalbitz, 2003;Rees and Parker, 2005), but surprisingly the WEOC degree of aromaticity normally used as a proxy of WEOC biodegradability (Marschner and Kalbitz 2003) was not found as a driver of soil enzyme activity under the climate change (Gavazov et al, 2014). The accumulation of freePOM due to lower enzyme potential activities (Fig 4.B) adds further support for fresh plant material accumulation.…”
Section: -Discussionsupporting
confidence: 56%
“…The variance in soil gravimetric moisture was largely explained by our climate change manipulation (R 2 =0.53* and R 2 =0.59**; linear model for winter and summer season respectively) confirming that this variable integrates the effect of the climate change manipulation. Moreover, previous investigations of the same soil transplantation experiment revealed the prevailing soil moisture vs temperature controls on soil C turnover (Mills et al 2014) and (Gavazov et al 2014). C-enzymes potential activities were split into hydrolase enzymes (mean of ß-glucosidases, cellobiohydrolase, xylosidase, lipase) and oxidase enzyme (phenol oxidase) (Table 1).…”
Section: Structural Equation Modelling (Sem)mentioning
confidence: 91%
“…The predominance of recalcitrant metabolites that are resistant to enzymatic (microbial) and environmental degradation was suspected to reduce litter mass loss in the later phase [5,10,42]. Litter decomposition can be principally divided into the early phase (before 20-40% mass loss), determined by the initial litter chemistry, while the later phase is mainly controlled by the decomposition of the lignin and the microbial community [34,50,51]; our study has demonstrated the early phase of decomposition.…”
Section: Litter Decomposition In Different Land Use Types Along the Ementioning
confidence: 60%
“…Litter decomposition can be divided into two phases, and the early phase (up to 20-40% of the total mass loss) is mainly determined by litter chemistry, while the later phase is mainly controlled by the microbial community (Berg & McClaugherty, 2008;Bray, Kitajima & Mack, 2012;Gavazov et al, 2014). Meanwhile, litter decomposition is an ecological process governed by decomposer organisms, and therefore, an increase in temperature is likely to stimulate litter decomposition by creating conditions favourable for decomposer communities and their activity (Davidson & Janssens, 2006;Chacon & Dezzeo, 2007;Cusack et al, 2009).…”
Section: Sources Of Deviationmentioning
confidence: 99%
“…Environmental gradients, especially elevation gradients, have been useful in quantifying the influence of environmental conditions on ecosystem processes (Dunne et al, 2004;Malhi et al, 2010;Sundqvist, Giesler & Wardle, 2011). Elevation gradient studies represent a natural approach to evaluate the impact of climatic parameters on ecological processes (K€ orner, 2007;Gavazov et al, 2014). Furthermore, ecological field experiments along elevation gradients allow for the discrimination between direct environmental factors and other site-dependent factors, such as species traits and composition (van de Weg et al, 2009;Pellissier et al, 2010;Averill & Finzi, 2011).…”
Section: Introductionmentioning
confidence: 99%